An Exploration of Secondary Students’ Perception of Blended Learning in Mathematics Learning - Intania Ayu Harjanti; Ayu Faradillah (SJME (Supremum Journal of Mathematics Education), 2020)
This study aims to analyze students’ perceptions about the use of blended learning models in understanding mathematics. As blended learning becomes more commonplace, it is important to assess whether students like or dislike the application of blended learning in their studies. The total research subjects were 319 secondary students from 6 different schools in Jakarta. Furthermore, this study used a survey method and the data were analyzed using the Rasch Model (WinSteps). The research instrument was a questionnaire consisting of 21 statements with several indicators, including the delivery of material, understanding of mathematical concepts, easy access, and assignments. Based on the wright maps table on WinSteps, the percentage of male students who like the Blended Learning model in learning mathematics is more than female students. Meanwhile, when viewed in terms of grade, 7th and 8th grade students like the application of blended learning models the most. In addition, this study reveals that students most dislike when it is difficult to access assignments online during the application of blended learning by teachers in learning mathematics. Therefore, to solve mathematical problems, students prefer to have a face-to-face interaction with the teachers to ask if there is something that is not understood yet.